25-Hydroxyvitamin D C3-epimer is universally present in neonatal Western Australian samples but is unlikely to contribute to diagnostic misclassification. (September 2016) - Cooke, David J; Cooke, Brian R; Bell, Damon A; Vasikaran, Samuel D; Glendenning, Paul
Background: The presence of C3-epimer (C-3-epi-25-hydroxyvitamin D) in infant serum may complicate 25-hydroxyvitamin D (25(OH)D) measurement when using liquid chromatography tandem mass spectrometry assays that do not separately measure the epimer. We measured the concentration of C3-epi-25(OH)D in neonatal samples in Western Australian using umbilical cord blood samples and a liquid chromatography tandem mass spectrometry assay that separately quantifies 25(OH)D and C3-epi-25(OH)D. Methods: A total of 120 anonymized cord blood samples were analysed using a liquid chromatography tandem mass spectrometry assay that utilizes two CSH fluoro-phenyl columns in series. Chromatography was performed on a Waters Acquity Ultra Performance Liquid system, and quantification was using a Waters Quattro Premier XE mass spectrometer. Results: C3-epi-25(OH)D3 was detected in all umbilical cord blood samples (median 5.2 nmol/L, IQR 3.7–6.6 nmol/L) and contributed 6.6% (SD 2.6, 95% CI [6.1, 7.1]) of the total 25(OH)D concentration. Mean 25(OH)D3 measured in cord blood was 79.1 nmol/L (SD 22.7 nmol/L). A positive relationship (R 2  = 0.35, P  < 0.0005) between 25(OH)D3 levels and C3-epi-25(OH)D3 was noted in this cohort. No samples contained 25(OH)D2 or C3-epi-25(OH)D2 . Conclusion: C3-epi-25(OH)D3 is present in all neonatal samples but contributes <10% of the total 25(OH)D concentration which is unlikely to be clinically significant. Liquid chromatography tandem mass spectrometry assays that do not separately quantify C3-epi-25(OH)D3 from other vitamin D metabolites may potentially overestimate neonatal 25(OH)D levels, but diagnostic misclassification in neonates is unlikely.